Improving oil recovery in Kazakhstan oilfields by using polyacrylamide - Yerzhan, Abylkhanov (2009)
This research presents a cross-linked polymer system (CPS), which is classified as a gel. Cross-linked polymers can be used in chemical enhanced oil recovery as an in-depth profile regulation agent, and at the same time as an oil dislocation agent in a heterogeneous reservoir. The cross-linked polymer gel system has comparatively low strength but it can still be cross-linked in the reservoir. The cross-linked polymer system comprises of polyacrylamide and chromium(III) acetate. The EOR mechanisms of the cross-linked polymer system are reported in detail. The effects of temperature, concentration, pH value on gelation time, rheological properties, gelation range, and gel strength were examined in this research. The Treeys-Pylot software was used in this research for simulations and efficiency prediction. The simulation results were found to have given clear evidence that the CPS succeeded in developing the injection profile which has increased the sweep efficiency. This in turn increased the oil recovery. Moreover, CPS treatment has been done in Dakes oil field in Kazakhstan since 2002. It was found that the CPS can improve oil recovery and effectively reduce water breakthrough. By the end of 2006, the cumulative oil production had been over 821,115 bbl. The predicted and real efficiency data were successfully correlated. The correction coefficient for Treeys-Pylot Software was obtained and equal to 0.85. Akbiken oilfield in Kazakhstan also has problem with water breakthrough. This research suggests using the CPS technology to solve this problem. Both oilfields are very similar, thus the obtained correction coefficient can be used for Akbiken oilfield. The efficiency can be correctly predicted using this coefficient.